(untitled) (Our Nature, 2025)
This study comprehensively examined Lepidoptera diversity in the semi-urban agricultural landscapes of Lumbini, Nepal, documenting 30 moth species from six families and 39 butterfly species from five families over 14 days. Field methods included moth traps with 50-watt LED lights inside a box lined with egg cartons for moth trapping, as well as butterfly transect surveys across various habitats, including grasslands, shrublands, and agricultural areas, for recording butterfly species. The Erebidae family dominated moth populations, while Nymphalidae led butterfly diversity, showing resilience in disturbed habitats influenced by environmental factors such as weather patterns, lunar phases, and habitat characteristics. Statistical analyses using Simpson’s Diversity Index, Shannon-Wiener Diversity Index, Pielou’s Evenness Index, and Margalef’s Richness Index revealed that shrubland and agricultural habitats supported the highest species richness and evenness, while grasslands hosted fewer species. The study highlighted the importance of agricultural and shrubland ecosystems for biodiversity, emphasizing ongoing monitoring to understand how Lepidoptera populations respond to environmental changes, offering essential insights for future conservation efforts.